Legal Certainty and Social Security: Two Main Pillars of the LLAJ Bill for the Future of Online Motorcycle Taxi Drivers - Martitah, Martitah; Dewi Sulistianingsih; Salsabila, Arini; Anggeraeni, Ayuk; Fatmawati, Dewi (The Indonesian Journal of International Clinical Legal Education, 2025)
The era of digitalization has brought about significant transformation in Indonesia's transportation sector through the emergence of online motorcycle taxis (ojol). However, despite their significant contribution to the economy and employment, ojol drivers face two fundamental problems: the lack of legal certainty regarding their employment status and the lack of adequate social security. This study aims to analyze the extent to which the draft Law on Road Traffic and Transportation (RUU LLAJ) currently under discussion can address these two issues. Using normative legal research methods and a descriptive-analytical approach, this article analyzes primary and secondary legal materials through the lens of Gustav Radbruch's Theory of Legal Certainty and T.H. Marshall's Theory of the Welfare State. The results of the study show that the LLAJ Bill is projected to become a comprehensive legal umbrella to provide legal certainty for drivers and require platforms to provide social security. Thus, the LLAJ Bill is expected to become the foundation for the creation of a fair and sustainable digital transportation ecosystem in Indonesia.